(untitled) (Journal Of Educational and Psychological Researches, 2013)
The Feedback Concept has been spread as an organized trend for scientific research since it has a significant importance for human behavior and how it has been directed and controlled by the individual, feedback has numerous definitions but the simplest definition is; feedback is the information received by the individual from the output of his behavior, In addition to the mutual relationship between the individual and the stimulation that provide him with the basic information by the biological control of his behavior, Since feedback cannot be accomplished without receiving information from the inner and outer environment, the biological and physiological information become the main source for controlling the individual behavior which leads to the concept of (Bio-feedback). The bio-feedback is one of the concepts of the modern feedback and the most important in Applied physiological psychology Moreover, the biofeedback is considered a modern trend which has been developed in the beginning of the sixties of the last century, In spite of its recent development, it has been proved that it is a modern flexible therapeutically training process based on scientific significant principles, furthermore the programmed education is one of the most modern training and educating methods which is based on self control and discipline behavior performed on the basis of feedback and resulted from the individual’s activities without having any side effects, the biofeedback systems is one of the expert systems specialized in examining, diagnosing, psycho therapy, neurological, psycho neurological, muscular, physiological and its use of knowledge training and physiotherapy, biofeedback is considered one of the modern discoveries in the computer and technological treatment based on supplementary and non-allopathic medicine, Different neurological, psychological, and physical diseases can be treated by this system, In addition to psychosomatic physical diseases, postwar psychological disorders, physiotherapy and rehabilitation for the disabled, addicted treatment, breathing training, relaxation, and decreasing stress and anger….etc.